Property in Licences and the Law of Things - Essert, Christopher (McGill Law Journal / Revue de droit de McGill, 2014)
A theoretical account of property rights needs to identify what, if anything, is distinctive about property rights as opposed to other sorts of rights; what makes them the sorts of rights that they are. An important and prominent account of the distinctiveness of property rights claims that they are rights to things. I argue against this view: I show that a government-issued licence (to fish or to drive a taxi or to operate a radio station, say) is not a right to a thing but should nevertheless count as a property right. I consider two different arguments for this rights-to-things view: one is based on the Hohfeldian structure of property rights, and one relies on the importance of information costs in the law of property. While each of these arguments teaches us important lessons about property, none can properly support the conclusion that property is rights to things. I suggest that abandoning the rights-to-things view of property can lead to important insights into property theory more generally.